2017
DOI: 10.1002/wps.20386
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of psychosis spectrum symptoms in the Philadelphia Neurodevelopmental Cohort: a prospective two‐year follow‐up

Abstract: Prospective evaluation of youths with early psychotic-like experiences can enrich our knowledge of clinical, biobehavioral and environmental risk and protective factors associated with the development of psychotic disorders. We aimed to investigate the predictors of persistence or worsening of psychosis spectrum features among US youth through the first large systematic study to evaluate subclinical symptoms in the community. Based on Time 1 screen of 9,498 youth (age 8-21) from the Philadelphia Neurodevelopme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 64 publications
8
125
3
Order By: Relevance
“…For example, birth cohort studies have found that PEs were more common in children with (a) lower intelligence (35), (b) cognitive deficits such as slower processing speed (36), or (c) neurodevelopmental disorders including dyslexia, dyspraxia and related problems (37). Thus, both PEs and disability may be downstream consequences of neurodevelopmental disorders (38), rather than causally related. Regardless of the causal pathways, our findings indicate that those with PEs are more disabled.…”
Section: Discussionmentioning
confidence: 99%
“…For example, birth cohort studies have found that PEs were more common in children with (a) lower intelligence (35), (b) cognitive deficits such as slower processing speed (36), or (c) neurodevelopmental disorders including dyslexia, dyspraxia and related problems (37). Thus, both PEs and disability may be downstream consequences of neurodevelopmental disorders (38), rather than causally related. Regardless of the causal pathways, our findings indicate that those with PEs are more disabled.…”
Section: Discussionmentioning
confidence: 99%
“…A complementary approach may be based on the use of sequential testing methods. The sequential use of screening instruments and CHR‐P assessment in non‐help‐seeking adolescents from the general population may identify individuals who are at potential risk of developing psychosis in the following years. Sequential testing is in line with the clinical staging model and can be further enhanced by front‐line primary care youth mental health models developed to facilitate the access of young people from the school and community (see https://www.headspace.org.au).…”
Section: Primary Preventionmentioning
confidence: 99%
“…In the majority of cases, PE are transient phenomena. It has previously been reported that PE, even when transient, is associated with increased risk of subsequent psychopathology (Calkins et al, ). However, there is also evidence that this relationship may be confounded by baseline psychopathology, and after accounting for this, there is no longer a relationship between transient PE and subsequent psychopathology (Downs, Cullen, Barragan, & Laurens, ).…”
Section: Introductionmentioning
confidence: 97%
“…In the majority of cases, PE are transient phenomena. It has previously been reported that PE, even when transient, is associated with increased risk of subsequent psychopathology (Calkins et al, 2017).…”
Section: Introductionmentioning
confidence: 99%